Update on Clinical Trials in Dry Age-related Macular Degeneration - Taskintuna, Ibrahim (Middle East Afr J Ophthalmol, 2016)
This review article summarizes the most recent clinical trials for dry age-related macular degeneration (AMD), the most common cause of vision loss in the elderly in developed countries. A literature search through websites https://www.pubmed.org and https://www.clinicaltrials.gov/, both accessed no later than November 04, 2015, was performed. We identified three Phase III clinical trials that were completed over the recent 5 years Age-Related Eye Disease Study 2 (AREDS2), implantable miniature telescope and tandospirone, and several other trials targeting a variety of mechanisms including, oxidative stress, complement inhibition, visual cycle inhibition, retinal and choroidal blood flow, stem cells, gene therapy, and visual rehabilitation. To date, none of the biologically oriented therapies have resulted in improved vision. Vision improvement was reported with an implantable mini telescope. Stem cells therapy holds a potential for vision improvement. The AREDS2 formulas did not add any further reduced risk of progression to advanced AMD, compared to the original AREDS formula. Several recently discovered pathogenetic mechanisms in dry AMD have enabled development of new treatment strategies, and several of these have been tested in recent clinical trials and are currently being tested in ongoing trials. The rapid development and understanding of pathogenesis holds promise for the future.